Dielectric and transient electrical response of SmB6 single crystals. (March 2023) - Stankiewicz, Jolanta; Schlottmann, Pedro; Blasco, Javier; Hatnean, Monica Ciomaga; Balakrishnan, Geetha
Highlights: SmB6 dielectric response at low temperatures reveals crucial role of surface in impedance spectra. Equivalent inductance drops drastically as bulk starts to control conductivity. SmB6 micro-crystals are excellent candidates for tunable oscillators. Graphical abstract: Abstract: We report results from an in–plane and out–of–plane impedance study on SmB6 single crystals, performed at low temperatures and over a wide frequency range. A universal equivalent circuit describes the dielectric behavior of this system across the transition, from surface to bulk dominated electrical conduction between 2 and 10 K. We identify the resistive, capacitive, and inductive contributions to the impedance. The equivalent inductance, obtained from fits to experimental data, drops drastically with increasing temperature, as the bulk starts to control electrical conduction. Self–sustained voltage oscillations, observed below 6 K across small crystals when biased with a dc current, point to a large SmB6 self–capacitance, likely brought by the surface states.